2021
DOI: 10.3389/feduc.2021.658011
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Factors That are Associated With Teachers’ Intentions to Utilize Research in Remote Areas of Greece

Abstract: Teachers around the world, serving in remote areas experience professional isolation (Bouck, 2004). In addition to being geographically isolated, challenges to remote teaching include a lack of professional support (Ralph, 2002) and experience of social isolation. Yet, the utilization of educational research has the potential to alleviate this issue. Therefore, this study examines the interplay between the factors that can possibly explain the teacher’s intentions to use research for professional development p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Importantly, recent research has suggested a link between body image dissatisfaction and test anxiety. For instance, Trikoilis (2023) found that body image dissatisfaction affected adolescents' test anxiety by reducing their physical activity. Therefore, test anxiety might be a more pertinent mediator in the relationship between body image dissatisfaction and academic buoyancy.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, recent research has suggested a link between body image dissatisfaction and test anxiety. For instance, Trikoilis (2023) found that body image dissatisfaction affected adolescents' test anxiety by reducing their physical activity. Therefore, test anxiety might be a more pertinent mediator in the relationship between body image dissatisfaction and academic buoyancy.…”
Section: Discussionmentioning
confidence: 99%